Comparison of interior permanent magnet synchronous machines for a high-speed application - Kalyan, Mohamedreza (Department of Electrical Engineering, 2019)
Permanent Magnet machines have been increasingly used in high-speed applications due to the advantages they offer such as higher efficiency, output torque and, output power. This dissertation discusses the electrical and magnetic design of permanent magnet machines and the design and analysis of two 10 kW, 30000 rpm Interior Permanent Magnet (IPM) machines. This dissertation consists of two parts: the first part discusses high-speed machine topologies, and in particular the permanent magnet machine. Trends, advantages, disadvantages, recent developments, etc. are discussed and conclusions are made. The second part presents the design, analysis and testing of interior permanent magnet machines for a high-speed application. The machines are designed from first principles and are simulated using Ansys Maxwell software to understand the finite element analysis. In order to obtain a fair comparison between the machines, the required output criteria was used as the judging criteria (10kW, 30000 rpm). As a result, the rotor diameter, stator diameter, airgap length, and stack length were kept the same for both machines. The winding configuration was set as distributed windings, however the number of turns and other details were kept flexible in order to be able to obtain the best design for each machine. Similarly, the magnet volume was kept flexible as this could be used as a comparison criteria relating to the cost of the machines. The two IPM topologies are compared with respect to their torque, magnetic field, airgap flux, core loss, efficiency, and cost. The radial IPM produces a smoother torque output, with lower torque ripple, and has lower losses compared to the circumferential IPM which produces a higher torque and power output. Furthermore, the circumferential IPM also experiences much higher torque ripple and core losses, both of which are highly undesirable characteristics for high-speed machines. In addition, the circumferential IPM has a much more complex manufacturing process compared to the radial IPM which would significantly increase the cost of prototyping the machine, thus the radial IPM was selected for prototyping and brief experimental analysis. The radial IPM has been experimentally tested under no-load conditions. These results were successfully compared to the simulated and analytical results to show correlation between the design and experimental process. Potential areas of further work may include conducting detailed loss analysis to understand the effects that changing various design parameters has on the core loss and overall performance. Detailed thermal and mechanical analysis of the machines may also result in interesting conclusions that would alter the design of the machine to make it more efficient.